Thermal changes in the pulp chamber during different adhesive clean-up procedures - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2005)
The aim of this in vitro study was to measure the temperature changes in the pulpal chamber when different adhesive clean-up procedures were used. Ninety intact extracted human maxillary central incisors were used in the study. The teeth were divided into six groups of 15 teeth each. The removal of the remaining composite on the tooth surface was performed with a tungsten carbide bur. The residual adhesive was removed using a high-speed handpiece with and without water cooling and a contra-angle handpiece with and without water cooling at high and low speeds. A J-type thermocouple wire was positioned in the center of the pulp chamber. The results were analyzed with analysis of variance (ANOVA) and the Tukey-honestly significant difference test. Two-factor ANOVA revealed significant interaction between the handpiece type and water cooling. In this study, the high-speed contra-angle handpiece without water cooling group had the highest Delta T values (7.58 degrees C +/- 1.84 degrees C) among all the clean-up procedures. The decrease in pulpal temperature with water cooling was -5.34 degrees C for the handpiece, -5.36 degrees C for the lowspeed contra-angle handpiece and -4.98 degrees C for the high-speed contra-angle handpiece. Clinicians should be aware of the potential thermal damage to the pulp, which may result from long clean-up procedures without water cooling. Adhesive removal procedures should be performed with adequate water cooling to prevent temperature increases that might be harmful to pulpal tissues.
Keywords: clean-up; temperature; pulp chamber; thermocouple; ENAMEL SURFACE; INTRAPULPAL TEMPERATURE; ORTHODONTIC BRACKETS; DEBONDING TECHNIQUES; REMOVAL; LASER; HEAT